GULMA TEKI-TEKIAN DI KEBUN KELAPA SAWIT DESA MAKMUR JAYA, TIKKE RAYA, KABUPATEN PASANGKAYU - Slamet Mardiyanto Rahayu (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2019)
One area that has oil palm plantations is Makmur Jaya Village, Tikke Raya District, Pasangkayu Regency (formerly called North Mamuju Regency), West Sulawesi Province. One of the problems in the cultivation of oil palm is weeds. This study aims to determine the types of puzzle weeds in the oil palm plantation in Makmur Jaya Village, Tikke Raya District, Pasangkayu Regency, West Sulawesi Province. Based on the research, there were 3 types of puzzle weeds in the Makmur Jaya Village oil palm plantation, namely Cyperus compressus, C.rotundus, and Fimbristylis milliacea. Riddle weeds have leaves similar to narrow-leaf weeds, but have a mendong stem (consisting of only one long segment) and are also triangular in shape. Riddle weeds have allelopathic compounds which make it difficult for palm oil plants to grow.